The increases in children entering public care in Wales: What does linked administrative data tell us? - Warner, Nell (International Journal of Population Data Science, 2025)
Objectives To find out whether the increases in children entering care are related to either increases in parental risk factors for care entry and/or any changes in the impact that a parental risk factors have on the likelihood of care. Method Three cohorts were created of households with children in Wales covering four-year periods between 2008 and 2020. Households that had at least one child aged 3 to 17 enter care were identified using children’s social care data. Risk factors in adults in the households were identified from health care datasets. Descriptive statistics were used to compare the prevalence of risk factors in the adults in the households in each cohort, and attributable fractions and excess cases calculated. Logistic regression models were used to look at the impact of the risk factors on the likelihood of care in each cohort. Results The prevalence of some risk factors changed over time, with depression and anxiety showing the greatest increases, while alcohol misuse and severe mental health problems appear to decrease slightly. Depression and anxiety appear to account for greater numbers of excess cases in later cohorts. Depression and attention deficit hyperactivity disorder have a greater impact on the odds of care in later cohorts, while the impact of other risk factors did not change much over cohort. Conclusion Findings suggest that some increases in care entry are related to increasing common mental health problems in adults and the relationship between depression and the likelihood of care entry.